Levels of Empathy and Their Association with Demographic and Academic Characteristics in Physical Therapy Students. - Sanchez, Isabel; Ulfe, Manuela; Mesías-Bermejo, Schirley; Bravo-Cuccia, Sergio (Cuestiones de Fisioterapia, 2025)
Introduction: Empathy is considered the central axis for achieving a good relationship between doctor and patient, with the aim of providing high-quality medical care.Objective: To examine empathy levels and determine their association with demographic and academic characteristics in Physical Therapy students from a private university in Lima, Peru.Methods: A descriptive cross-sectional quantitative study was conducted in Lima, Peru. The sample consisted of 118 participants. The Jefferson Scale of Physician Empathy was used to identify the level of empathic orientation in the students.Results: Data from 118 participants were used. The average total score for the Jefferson Scale of Physician Empathy questionnaire was 86.9 (SD: 9.61). 51.7% of participants showed a high level of empathy. It was found that the group of women had an average score of 89.1 (SD: 8.54), while men had an average score of 85.7 (SD: 9.99), suggesting that women have more empathy than men.Conclusions: A notably high level of empathy was observed among the Physical Therapy students. Academic trajectory does not modulate this empathy, indicating a predominantly innate nature of it.